Analisis Sosiologi Hukum Atas Tindak Pidana ITE: Studi Kasus Pemerasan Dan Pengancaman Yang Merugikan Hak Orang Lain - Rafid Herfindo (Judge : Jurnal Hukum, 2025)
Legal protection of the rights of victims of extortion and threats in the digital age has become an increasingly pressing issue. Criminal acts related to the Electronic Information and Transactions Law (ITE) demonstrate that perpetrators often exploit technology to record and threaten victims. This study analyzes the application of ITE law in the context of extortion and threats, as well as the challenges faced by the judicial system in addressing cybercrime. Through the case study of Decision Number xxx/Pid.Sus/2024/PN JKT.TIM, this research highlights the importance of restoring victims' rights, which includes financial compensation, psychological rehabilitation, and protection from further threats. Sociology of law provides an important perspective in understanding the interaction between law and society, as well as how social norms influence law enforcement. Recommendations for improving the legal system include enhancing training for law enforcement officials and fostering collaboration among various parties to create a safer environment. This research is expected to contribute to the development of legal sociology theory and law enforcement practices in Indonesia.